RF CMOS 공정을 이용한 5 GHz 대역 전압제어발진기와 8/9 주파수 분주기 설계 - 이동현 (The Graduate School, Ajou University, 2005)
In this thesis, a 5 GHz voltage controlled oscillator and 8/9 dual modulus prescaler for direct conversion application is designed and fabricated using Hynix 0.18 um RF CMOS process. The frequency synthesizer design for direct conversion application has DC offset and frequency pulling problems. Thus, the way to solve these problems is required. In this thesis, the solution is proposed. The fabricated VCO is composed of inductor, varactor, PMOS and NMOS Transistors of latch type. The VCO achieves the phase noise of -124 dBc/Hz at 1 MHz offset from 2.11 GHz with bias of 4.6 mA, 1.8 V. The power consumption is about 8.3 mW. The designed 8/9 dual modulus prescaler achieves a maximum operating frequency 10 GHz with bias of 6.2 mA, 1.8 V. The power consumption is about 11.26 mW.
학위논문(석사)--아주대학교 대학원 :전자공학과,2005